Notes on the Morphology and Systematic Position of Archaeolus Lin, 1986, from the Jurassic of South China (Coleoptera: Elateroidea) - Li, Yan-Da; Kundrata, Robin; Huang, Di-Ying; Cai, Chen-Yang (Insects, 2021)
The morphology of the Jurassic fossil Archaeolus funestus Lin, 1986, which was previously placed in the extinct click-beetle subfamily Protagrypninae (Coleoptera: Elateridae), is revised based on a re-examination of the type specimen. The validity of Protagrypninae is discussed and further questioned, partly based on the newly observed characters in A. funestus, including the surface sculpture of the mesoventrite. A possible Throscidae affinity of monotypic Archaeolus Lin, 1986, as suggested in a recent study, is further critically reviewed.
Keywords: Protagrypninae; Archaeolus; Elateroidea; Mesozoic; Throscidae